2022
DOI: 10.1007/s00705-022-05407-9
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus VP6: involvement in immunogenicity, adjuvant activity, and use as a vector for heterologous peptides, drug delivery, and production of nano-biomaterials

Abstract: The first-generation, live attenuated rotavirus (RV) vaccines, such as RotaTeq and Rotarix, were successful in reducing the number of RV-induced acute gastroenteritis (AGE) and child deaths globally. However, the low efficacy of these first-generation oral vaccines, coupled with safety concerns, required development of improved RV vaccines. The highly conserved structural protein VP6 is highly immunogenic, and it can generate self-assembled nano-sized structures, including tubes and spheres (virus-like particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…We further confirmed that the induced anti-BRV VP6 antibodies exhibited cross-reactivity with a closely related, yet heterologous, Group A rotavirus strain, i.e., the simian rotavirus SA11 strain (Additional file 4 A). This cross-reactivity could be attributed to the substantial conservation of VP6 antigenicity among Group A rotaviruses [ 36 38 ]. Further, we confirmed neutralizing activity against the simian rotavirus using sera collected from mice inoculated with rNDV-WT-VP6 (Additional files 4 B–D).…”
Section: Resultsmentioning
confidence: 99%
“…We further confirmed that the induced anti-BRV VP6 antibodies exhibited cross-reactivity with a closely related, yet heterologous, Group A rotavirus strain, i.e., the simian rotavirus SA11 strain (Additional file 4 A). This cross-reactivity could be attributed to the substantial conservation of VP6 antigenicity among Group A rotaviruses [ 36 38 ]. Further, we confirmed neutralizing activity against the simian rotavirus using sera collected from mice inoculated with rNDV-WT-VP6 (Additional files 4 B–D).…”
Section: Resultsmentioning
confidence: 99%
“…Different groups could be found in different hosts. However, group A, also shown with Rotavirus A (RVA), was highly prevalent in humans, swine, and poultry ( 2 ). Epidemiologically, RV has a nearly 50-year history from the preliminary report in the State of Alaska to the present.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the rotavirus capsid protein VP6 self-assembled VLP, which carried DOX by covalent conjunction also showed promising delivery of the drug into cultured cells. Modification of the VLP with lactobionic acid (LA) which binds to asialoglycoprotein receptors (ASGPRs) on the surface of the hepatoma cell line, showed specific delivery of the drugs to the HepG2 cells [51,79]. In addition, targeted delivery of the drug could be guided by single chain fragment variable (scFv) modified VLPs.…”
Section: Vlps For Compound Deliverymentioning
confidence: 99%